Au-delà de ce qui semble déterminé : « Façonner » les nouveau-nés inuit dans le Kivalliq contemporain (Note de recherche) - Rodrigue, Julie (Anthropologie et Sociétés, 2007)
“When an elder tells you something while you are a baby it becomes true. You have to be very careful with your words”, says an elder from Kivalliq. Forher, and many other elders, the birth of a child is a period of transition marked by instability and fragility. Relations between the newborn and a namesake certainly influence the infant’s personality, but there exists a latitude beyond what seems to be determined. The acts, gestures, sentiments, words that are spoken or thought about a newborn have particular power. For better or for worst, these practices « shape » the Inuk and will have great impact on his/her life. « When an elder tells you something while you are a baby it becomes true. You have to be very careful with your words », confie une aînée de la région du Kivalliq. Pour cette aînée, comme plusieurs autres de la région, la naissance d’un nouveau-né est une période de transition empreinte d’instabilité et de fragilité. Les relations entre éponymes ont une influence certaine sur la personnalité, mais au-delà de ce qui est déterminé, une certaine latitude semble possible. Les actions, les gestes, les sentiments et les mots dits ou pensés revêtent un pouvoir particulier. Pour le meilleur ou pour le pire, ces pratiques « façonnent » l’Inuk et elles marqueront le fil de son existence. « When an elder tells you something while you are a baby it becomes true. You have to be very careful with your words » (Kangiq&iniq 2004). Para esta anciana, como para muchos otros ancianos de la región de Kivalliq, el nacimiento de un recién nacido es un periodo de transición marcado por la inestabilidad y la fragilidad. Las relaciones entre epónimos tienen una influencia sobre la personalidad, pero más allá de lo que determinan, una cierta latitud parece posible. Las acciones, los gestos, los sentimientos y las palabras pronunciadas o pensadas revisten un poder particular. Para lo bueno y para lo malo, dichas practicas « fabrican » l’Inuk y marcarán el hilo de su existencia